Moving from Fossil Fuels to Electric Cooking: An Option for Clean Cooking Access in Nepal - Kafle, Samikchhya; Mishra, Arabinda Kumar; Maharjan, Amina; Panday, Arnico Kumar (Journal of the Institute of Engineering, 2020)
Nepal has abundant hydropower potential and generation capacity under construction that should be able to meet the growing energy need of the country. Although access to electricity in the country is increasing, adoption and access to clean cooking facilities remains insignificant, as about 85% of the population still rely on solid fuels to meet their daily cooking needs. In this regard, energy generated from hydropower can play the dual role of providing access to modern energy as well as providing a clean cooking alternative that is clean and sustainable. Having realized this, the Ministry of Energy, Water Resources and Irrigation has issued a white paper (point 73) for the ‘Electric Stove in Every House’ Programme, which is expected to encourage the use of electric cooking. This gives an opportunity not only to make use of Nepal’s hydropower resources but also to reduce its dependence on imported fossil fuel. Our paper discusses the challenges and opportunities for introducing electricity in the cooking fuel mix in Nepal from the policy perspective. We draw upon the review of lessons learned from other countries including Ecuador, Bhutan and South Africa, to illustrate the potential pathways for the transition of fossil fuel-based products to electricity in Nepal. These countries have used a combination of approaches in including electricity in their cooking fuel mix, such as favourable electricity pricing, import tariff reductions in cooking appliances, and developing national policy and programmes to facilitate the integration of electricity in cooking fuel. These lessons from these countries are used to recommend pathways for moving from fossil fuel-based products to electricity in Nepal’s context.